2018
DOI: 10.2340/16501977-2345
|View full text |Cite
|
Sign up to set email alerts
|

Usability of World Health Organization Disability Assessment Schedule in chronic traumatic brain injury

Abstract: Patients with chronic traumatic brain injury perceive a diversity of significant difficulties in activities and participation irrespective of the severity of the injury. We recommend assessing disability in traumatic brain injury with the short and understandable WHODAS 2.0 scale, when planning client-oriented services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Furthermore, it has previously been shown that more symptoms in patients with bipolar disorder were related to higher ratings on WHODAS [29], while less symptoms were related to lower ratings. The same relationship between symptom severity and WHODAS ratings has been found in patients with traumatic brain injury and stroke [30,31]. Patients' own reports might also be biased due to unawareness of their difficulties [32], something that could have influenced the ratings by patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, it has previously been shown that more symptoms in patients with bipolar disorder were related to higher ratings on WHODAS [29], while less symptoms were related to lower ratings. The same relationship between symptom severity and WHODAS ratings has been found in patients with traumatic brain injury and stroke [30,31]. Patients' own reports might also be biased due to unawareness of their difficulties [32], something that could have influenced the ratings by patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies of WHODAS 2.0 in stroke patients have usually been based on a longer version of this scale (36). The aim of the current study was to identify as simple validated functioning scales as possible, and the 12-item WHODAS 2.0 was found suitable, especially as, in previous studies among patients with amyotrophic lateral sclerosis, traumatic brain injury, spinal cord injury and spinal pain (20)(21)(22)(23)(24), this measure was easy to apply for both patients and significant others. As WHODAS includes not only activities, but also items of participation, it provides a wider perspective for goal-setting and service-planning than the conventional instruments.…”
Section: Discussionmentioning
confidence: 96%
“…To unify the assessment of functioning globally, regardless of health condition, the World Health Organization (WHO) has developed a generic patient-and proxy-reported instrument to measure both activities and participation, the WHO Disability Assessment Schedule (WHODAS 2.0), which has been validated in various conditions, including stroke (18). The short 12-item form of WHODAS 2.0 has been found to be practical for use in various clinical settings (19)(20)(21)(22)(23)(24). Another short ICF-based instrument, the 7-item WHO Minimal Generic Set of domains of functioning and health, has been suggested for use as a starting point to address comparability of data across studies (25).…”
mentioning
confidence: 99%
“…Higher scores indicate greater perceived disability. It has been previously validated for use in mTBI (Herrold et al, 2019; Snell et al, 2017, 2020; Tarvonen-Schröder et al, 2018). Internal consistency (Cronbach’s alpha at the 1-month assessment) in the present sample was 0.93.…”
Section: Methodsmentioning
confidence: 99%